Functional Pairing of Class B1 Ligand-GPCR in Cephalochordate Provides Evidence of the Origin of PTH and PACAP/Glucagon Receptor Family - On, Jason S.W. (Mol Biol Evol, 2015)
Several hypotheses have been proposed regarding the origin and evolution of the secretin family of peptides and receptors. However, identification of homologous ligand–receptor pairs in invertebrates and vertebrates is difficult because of the low levels of sequence identity between orthologs of distant species. In this study, five receptors structurally related to the vertebrate class B1 G protein-coupled receptor (GPCR) family were characterized from amphioxus (Branchiostoma floridae). Phylogenetic analysis showed that they clustered with vertebrate parathyroid hormone receptors (PTHR) and pituitary adenylate cyclase-activating polypeptide (PACAP)/glucagon receptors. These PTHR-like receptors shared synteny with several PTH and PACAP/glucagon receptors identified in spotted gar, Xenopus, and human, indicating that amphioxus preserves the ancestral chordate genomic organization of these receptor subfamilies. According to recent data by Mirabeau and Joly, amphioxus also expresses putative peptide ligands including homologs of PTH (bfPTH1 and 2) and PACAP/GLUC-like peptides (bfPACAP/GLUCs) that may interact with these receptors. Functional analyses showed that bfPTH1 and bfPTH2 activated one of the amphioxus receptors (bf98C) whereas bfPACAP/GLUCs strongly interacted with bf95. In summary, our data confirm the presence of PTH and PACAP/GLUC ligand–receptor pairs in amphioxus, demonstrating that functional homologs of vertebrate PTH and PACAP/glucagon GPCR subfamilies arose before the cephalochordate divergence from the ancestor of tunicates and vertebrates.